2018
DOI: 10.1152/japplphysiol.00137.2018
|View full text |Cite
|
Sign up to set email alerts
|

Exercise preconditioning diminishes skeletal muscle atrophy after hindlimb suspension in mice

Abstract: The aim of the present study was to investigate whether short-term, concurrent exercise training before hindlimb suspension (HLS) prevents or diminishes both soleus and gastrocnemius atrophy and to analyze whether changes in mitochondrial molecular markers were associated. Male C57BL/6 mice were assigned to control at 13 ± 1 wk of age, 7-day HLS at 12 ± 1 wk of age (HLS), 2 wk of exercise training before 7-day HLS at 10 ± 1 wk of age (Ex+HLS), and 2 wk of exercise training at 11 ± 1 wk of age (Ex) groups. HLS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 56 publications
1
40
0
Order By: Relevance
“…When comparing the results of this meta‐analysis to other models of skeletal muscle atrophy, we found that a 7‐day hind limb suspension resulted in a comparable decrease in soleus (27.1%) and gastrocnemius muscle (21.5%) weight to body weight ratio in wildtype mice . Moreover, evidence shows that the network of interacting signalling pathways that we found to be involved in doxorubicin‐induced skeletal muscle atrophy, also share common pathways with disuse atrophy .…”
Section: Discussionmentioning
confidence: 57%
“…When comparing the results of this meta‐analysis to other models of skeletal muscle atrophy, we found that a 7‐day hind limb suspension resulted in a comparable decrease in soleus (27.1%) and gastrocnemius muscle (21.5%) weight to body weight ratio in wildtype mice . Moreover, evidence shows that the network of interacting signalling pathways that we found to be involved in doxorubicin‐induced skeletal muscle atrophy, also share common pathways with disuse atrophy .…”
Section: Discussionmentioning
confidence: 57%
“…Muscle mass is determined by the balance between muscle protein synthesis and degradation which control the accretion or loss of muscle mass (Figure ) . The primary mechanism for disuse atrophy seems to be the reduction in muscle protein synthesis in mice, rats and humans . Muscle protein synthesis is stimulated by the activation of mammalian target of rapamycin (mTOR) pathway, a key regulator of translation initiation and its downstream targets S6 kinase‐1 (S6K1) and 4E binding protein 1 (4E‐BP1).…”
Section: Methodsmentioning
confidence: 99%
“…The mechanisms involved in the production of the beneficial effects of preconditioning in skeletal muscle are not yet clear, although it has recently been shown to decrease skeletal muscle atrophy induced by the discharge of the hind limbs (HU) and the mechanism that can participate it is through HDAC4/Gadd45α [23]. Although, interestingly, the mechanisms of physical training to reduce muscle atrophy are associated with the biogenesis, function and redox balance of mitochondria, the same mechanism involved in preconditioning [24]. The redox mechanism seems to be common in preconditioning processes regardless of white tissue, probably not the only shared mechanism, but certainly unlike the cardiac muscle, in skeletal muscle hypertrophy represents a greater capacity for energy regulation.…”
Section: About Skeletal Musclementioning
confidence: 99%